2013
DOI: 10.1590/s1415-43662013000500003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chemical attributes of a Fluvent cultivated with castor bean and irrigated with wastewater

Abstract: Agricultural use of wastewater is an alternative to increase water availability, especially in semiarid regions. However, it may cause undesirable chemical changes in the soil. The aim of this study was to evaluate the influence of wastewater irrigation and castor bean (Ricinus communis L.) cultivation on the chemical attributes of a Fluvic Neosol. The experimental design was in a randomized block, in split-plot scheme, where the main plots were represented by the treatments of irrigation water and castor bean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
4
11
0
2
Order By: Relevance
“…In turn, Urbano et al (2015) concluded that the reuse of domestic effluents did not cause damage to the physical properties of the soil, but resulted in a tendency for salinization when irrigation was performed in undisturbed soil samples arranged in a constant load permeameter to simulate irrigation equivalent to 5 cycles of lettuce cultivation. Barreto et al (2013), similar to other authors, verified that after the application of wastewater to soil the levels of phosphorus, calcium, potassium and organic matter, mainly in the superficial layer (0 to 10 cm), and sodium, at depth (up to 50 cm), increased significantly compared with the application of water from public supply. In turn, Andrade Filho et al 2013, when applying different doses of the domestic effluent in Cambisol, observed that the attributes pH, MO, P, K + , Na + , Mg 2+ , Al 3+ and H+Al were significantly altered.…”
Section: Chemical Attributes Of the Soilsupporting
confidence: 90%
“…In turn, Urbano et al (2015) concluded that the reuse of domestic effluents did not cause damage to the physical properties of the soil, but resulted in a tendency for salinization when irrigation was performed in undisturbed soil samples arranged in a constant load permeameter to simulate irrigation equivalent to 5 cycles of lettuce cultivation. Barreto et al (2013), similar to other authors, verified that after the application of wastewater to soil the levels of phosphorus, calcium, potassium and organic matter, mainly in the superficial layer (0 to 10 cm), and sodium, at depth (up to 50 cm), increased significantly compared with the application of water from public supply. In turn, Andrade Filho et al 2013, when applying different doses of the domestic effluent in Cambisol, observed that the attributes pH, MO, P, K + , Na + , Mg 2+ , Al 3+ and H+Al were significantly altered.…”
Section: Chemical Attributes Of the Soilsupporting
confidence: 90%
“…Estes resultados diferem-se dos obtidos por Barreto et al, (2013), os quais não constataram alterações no pH do solo irrigado com efluente tratado. O pH encontrado denota acidez baixa e atende às exigências do rabanete, cujo ideal está entre 5,5 e 6,0 (Trani et al, 1997).…”
Section: Resultsunclassified
“…Quanto ao fósforo e potássio, não foi observada diferença estatística entre os tratamentos, mas constatou-se acréscimo em seus valores. Os resultados obtidos estão coerentes com Barreto et al, (2013) solo, apresentou elevação em ambos os tratamentos, mesmo resultado observado por Barreto et al, (2013) em seu experimento.. O sódio presente na água de irrigação favorece a elevação da porcentagem de sódio trocável (PST) no solo, afetando as propriedades físicas e químicas e dificultando a atividade da água a ser utilizada pela planta (Sandri et al, 2009). Mesmo que discretamente era esperada essa elevação no tratamento com efluente tratado, devido ao fato do mesmo conter sais solúveis, havendo a sua adição à solução do solo.…”
Section: Resultsunclassified
“…Depending on the nutrients, wastewater may be a potential source of macro-(N, P and K) and micronutrients (Ca, Mg, B, Mg, Fe, Mn or Zn) [38][39][40]. Indeed, wastewater reuse has been proven to improve crop yield [37,[41][42][43][44] and result in the reduced use of fertilizers in agriculture [45][46][47][48].…”
Section: Benefits Of Agricultural Reusementioning
confidence: 99%